EFEKTIVITAS MODEL PEMBELAJARAN BERBASIS MASALAH (PBM) TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SMP NEGERI 1 PINANGSORI - Transusi Silaban; Marzuki Ahmad; Roslian Lubis (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2019)
ABSTRACT The aim of this study is to describe the effectiveness of using PBM learning model on students’ creative thinking ability at the eighth grade students of SMP Negeri 1Pinangsori. This research was conducted by applying experimental (one group pre test post test design) with 32 students as the sample and they were taken by using cluster random sampling technique from 217 students. Observation and test were used in collecting the data. Based on descriptive analysis, it was found: (a) the average of using PBM learning model was 3.5 (very good category) and (b) the average of students’ creative thinking ability before using PBM learning model was 50 (fair category) and after using PBL learning model was 77.96 (good category). Furthermore, by using pair sample ttest and help SPSS version 22, the result showed the significant value was less than 0.05 (0.000<0.05). It mean, PBM learning model was effective used on students’ creative thinking ability at the eighth grade students of SMP Negeri 1Pinangsori.